Human dignity and education – A Protestant view - Schweitzer, Friedrich (HTS teologiese studies, 2016)
Taking current discussions on the relationship between human dignity as a human right and education as his starting point the author pursues the possibility of interpreting this relationship from a Protestant perspective based on the biblical understanding of the likeness of God. Since this understanding has not been at the centre of the majority view in Protestant educational thinking the author tries to uncover a minority tradition that has made the likeness of God the basis of education (Melanchthon, Comenius, and others). In another step, the author describes four foundational perspectives for making the likeness of God and human dignity the basis for education today, addressing education beyond utilitarianism, justice in education and education for justice, interreligious education and special commitment to children’s rights. In all four respects Protestantism can make important contributions but there is also a need for the renewal of Protestantism’s understanding of education in light of future challenges.